The carbon almanac : it's not too late - Godin, Seth, ....- (New York : Portfolio Penguin, 2022)
When it comes to the climate, we don't need more marketing or anxiety. We need established facts and a plan for collective action. The climate is the fundamental issue of our time, and now we face a critical decision. Whether to be optimistic or fatalistic, whether to profess skepticism or to take action. Yet it seems we can barely agree on what is really going on, let alone what needs to be done. We urgently need facts, not opinions. Insights, not statistics. And a shift from thinking about climate change as a "me" problem to a "we" problem. The Carbon Almanac is a once-in-a-lifetime collaboration between hundreds of writers, researchers, thinkers, and illustrators that focuses on what we know, what has come before, and what might happen next. Drawing on over 1,000 data points, the book uses cartoons, quotes, illustrations, tables, histories, and articles to lay out carbon's impact on our food system, ocean acidity, agriculture, energy, biodiversity, extreme weather events, the economy, human health, and best and worst-case scenarios. Visually engaging and built to share, The Carbon Almanac is the definitive source for facts and the basis for a global movement to fight climate change. This isn't what the oil companies, marketers, activists, or politicians want you to believe. This is what's really happening, right now. Our planet is in trouble, and no one concerned group, corporation, country, or hemisphere can address this on its own. Self-interest only increases the problem. We are in this together. And it's not too late for concerted, collective action for change.
Includes index.
Keywords: Climate change; Global warming